Analisa Komentar Pornoteks Pada Akun TikTok Kinderflix.idn - Widuhung, Selvy Maria; Pranawukir, swahyu (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2024)
The lack of special shows for toddlers makes the presence of Kinderflix content on various social media such as Youtube, Instagram, and TikTok a favorite show that is immediately liked by toddlers in Indonesia. Unfortunately, this is not accompanied by public understanding, especially adult men who misinterpret the presence of the show, by issuing lewd comments leading to sexual harassment of the Kinderflix content host. This study will look at how netizen comments on the Kinderflix TikTok account are influenced by positive and negative perception factors using Qualitative research and content analysis methods and using the Miles and Huberman theory which seeks to dissect a case using three data classifications, namely data reduction, data presentation, and conclusion drawing. From this research, it is found that most of the comment writers in TikTok Kinderflix content are men, and there are some comments that lead to online sexual harassment. Although of course there are also positive comments for the educational content for toddlers. It is hoped that this research can make learning for all parties to be wiser in commenting on social media so that it can support quality content creators to advance and provide benefits to society.